Sistem Penyelesaian Sengketa dalam Buku Barih Balobeh Adat Nagari Sarilomak Perspektif Hukum Nasional - Martia Lestari; Wardatun Nabilah; Erick Firdanus (Jurnal Pendidikan dan Humaniora Rumbio, 2024)
This reseach examines the customary dispute resolution system in customary justice and how the position of customary justice in the national judicial justice system, the reseach conducted is a library reseach with a qualitative method of analyzing the existence of customary justice as a dispute resolution institution in the book Barih Balobeh Adat Nagori Sarilomak. The existence of customary courts has largely been abolished by Law Number 48 of 2009, but with the recognition of the existence of customary courts in this book raises questions, where is the position of customary courts and their legal strength, this issue has not been studied by other studies, the results of the reseach show that customary courts in the context of the Barih Balobeh Adat Nagori Sarilomak book are first-level courts in the realm of customary power, and can proceed to state courts if necessary. The existence of the judiciary at the present time is limited to non-litigation dispute resolution efforts, so that it still requires further processing to the state court to obtain state legal protection.